The Palais des Machines of 1889. Historical-structural Reflections - Javier Estévez Cimadevila; Isaac López César (VLC Arquitectura)
The Galerie des Machines of 1889 is present in most books on the history of architecture. There are, however, certain aspects of this building that merit a more in-depth study. Other elements have been incorrectly described in current and contemporary publications about the building. The aim of this article is to examine the place this building occupies in the historical development of metal arch structures, its precedents and the influence it has exerted on later buildings of a similar structure. On the other hand, there have also been contradictions concerning the materials used in the erection of the structure and the reasons behind using them, as well as the exact span achieved. This article will unequivocally resolve these issues.